PENGARUH MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN TERHADAP MOTIVASI BELAJAR SISWA DI MTS DARUL FALAH CUKANG BUNGUR TASIKMALAYA - Ade Ikbal; Ikbal Pauji, Ade; Indra Permana (Manajerial | Journal Manajemen pendidikan islam, 2025)
Student learning motivation is a crucial factor in supporting educational success and is influenced by various aspects, one of which is the management of educational facilities and infrastructure. Proper management of facilities and infrastructure is believed to create a conducive learning environment and encourage students’ enthusiasm for learning. This study aims to analyze the influence of facilities and infrastructure management on students’ learning motivation at MTs Darul Falah Cukang Bungur, Tasikmalaya Regency. This research employed a quantitative approach with a population of 78 students, while the sample consisted of 44 students selected through purposive sampling with a margin of error of 10%. The research instrument was a closed-ended questionnaire that had been tested for validity and reliability. The findings reveal that the management of facilities and infrastructure contributes 42.8% to students’ learning motivation. This indicates that the better the management of educational facilities, the higher the learning motivation. Meanwhile, 57.2% of motivation is influenced by other factors, such as strong intrinsic motivation to achieve, the aspiration to reach future goals, and persistence in overcoming challenges. Teacher and parental support also play an important role as external factors that strengthen students’ motivation to learn. These findings emphasize that although intrinsic factors and social support are equally dominant, optimal management of facilities and infrastructure remains an essential component in enhancing students’ learning motivation